2019
DOI: 10.1103/physrevd.100.026007
|View full text |Cite
|
Sign up to set email alerts
|

Phases of melonic quantum mechanics

Abstract: We explore in detail properties of two melonic quantum mechanical theories which can be formulated either as fermionic matrix quantum mechanics in the new large D limit, or as disordered models. Both models have a mass parameter m and the transition from the perturbative large m region to the strongly coupled "black-hole" small m region is associated with several interesting phenomena. One model, with UðnÞ 2 symmetry and equivalent to complex Sachdev-Ye-Kitaev, has a line of first-order phase transitions termi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 125 publications
1
52
3
2
Order By: Relevance
“…Tensor models were initially studied in zero dimension in the context of quantum gravity and random geometry [3,[14][15][16][17]. They were then studied in one dimension [18][19][20][21][22][23][24][25][26][27][28][29][30] (see also [4,31] for reviews) as a generalization of the Sachdev-Ye-Kitaev model [32][33][34][35][36][37] without quenched disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Tensor models were initially studied in zero dimension in the context of quantum gravity and random geometry [3,[14][15][16][17]. They were then studied in one dimension [18][19][20][21][22][23][24][25][26][27][28][29][30] (see also [4,31] for reviews) as a generalization of the Sachdev-Ye-Kitaev model [32][33][34][35][36][37] without quenched disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Several aspects of this system can be capture by a 2-dimensional Einstein-dilation theory, and this has generated a lot of research within the framework of NAdS 2 /NCFT 1 and related areas. See, for instance, [14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Recently the quantum chaotic property was also studied in a variety of deformations of the SYK model [13,14,[33][34][35][36][37][38][39][40]. Among these developments in [13] the authors considered a deformation of the SYK Hamiltonian by a random mass term and found that the quantum Lyapunov exponent decreases as the mass parameter is increased.…”
Section: Jhep08(2020)081 1 Introduction and Summarymentioning
confidence: 99%
“…Also, the connection between chaos and the thermalization property of the system implies that one cannot see whether the system is chaotic or not just by looking thermodinamic quantities such as the free energy [46]. Nevertheless, there are some examples [14,34] where we have multiple evidences that they are indeed correlated. It would be interesting to ask what kind of additional properties of a model can relate the chaotic/integrable transition and the Hawking-Page like transition indirectly, which will define an interesting class of theories.…”
Section: Jhep08(2020)081 1 Introduction and Summarymentioning
confidence: 99%